Personal Hygiene Practices in 5th Grade Elementary School Students - Nurhayati, Ria; Wuri, Sherly (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2020)
Background: Personal hygiene is something that needs to be taken care of especially in elementary school-aged children. Data from the Srondol Community Health Center states that in 2017 the fifth-highest number of diarrhea occurred in elementary school-aged children. SDN Srondol Kulon 02 is a health promoting elementary school in the city of Semarang. Based on School Health Unit data, in 2018 there were 52 students from SDN Srondol Kulon 02 referred to the public health center because of diarrhea and 13 students referred to because of toothache. The purpose of this study was to determine the factors that influence personal hygiene practices in 5th grade elementary school students at SDN Srondol Kulon 02. Methods: This study was observational analytic with cross-sectional approach using total sampling technique and questionnaire instrument. The sample was 98 5th grade students in SDN Srondol Kulon 02. Data was analyzed by using chi-square test and ordinal regression. Results: There was an influence between Knowledge (p= 0.037) attitudes (p= 0.009) support of teaching staff (p= 0.005) family support (p= 0.008) with personal hygiene practices and no influence between the support of health workers (p= 0.997) and PHBS facilities (p= 0.817) with personal hygiene practices. Conclusion: Support of teaching staff was the most influential in improving students’ personal hygiene practices.